Increasing the yield of wheat as the basic export crop of the agro-industrial complex of the Republic of Kazakhstan - Shakeyev, S.S.; Nevmatulina, K.А.; Vladimirov, Zh.; Nurmaganbetov, A.S.; Syzdykova, E.Zh. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of the work is to study the key problems of increasing the yield of wheat as a basic export crop, analyze the production of wheat in the nearest countries, consider the main world exporters and importers of wheat, and identify ways to increase the yield of wheat. The question of the development of this area of the agro-industrial complex is still open and requires the introduction of a number of innovative processes. Methods: The methodological basis of the study was general scientific analysis and synthesis, system analysis, methods of economic and statistical analysis and comparative analysis were used. Findings: The results of the study were the proposals of the authors to increase the level of productivity, such as: the creation of research laboratories; accessibility to obtain and the need to use mineral fertilizers, the need to train agricultural producers in the selection of mineral fertilizers, which not only increase grain yields and improve its quality; selection work and much more. Conclusions: The study by the authors of the problems of increasing the level of wheat yields showed a direct dependence of production indicators and the volume of exports of wheat of the republic on its yield.